Comparative assessment of vegetable yield with and without biochar derived from locally sourced apricot shells - Sajad Hussain; Pratima Gajbhiye; Md Irfanul Haque Siddiqui; Chandrakant Sonawane; Dan Dobrotă (Scientific Reports)
Abstract Extreme climatic conditions and isolation from the rest of the world make it extremely challenging and difficult to obtain green vegetables in Kargil during the winters. Application of biochar enhances the productivity of vegetables during the short agricultural season so that the dry vegetable available throughout the winter. This research evaluates the potential use of biochar made from local apricot (Prunus armeniaca) seed shells (ASSBC) as a viable soil enhancer in the agriculturally difficult terrains of Kargil. Four vegetables that are relevant to the area selected for the investigations: spinach, lettuce, root beet, and mustard. Local veggie food security depends on these vegetables, especially around the winter when fresh green vegetables are unavailable. The shells of apricots, which were once considered trash, were collected, rinsed with distilled water, dried, crushed into uniform fragments, and then subjected to pyrolysis in nitrogen-laden conditions to form biochar. The obtained biochar was added to the soil kept in color coded experimental jars at a rate of 8%. The findings indicated that the number and size of leaves for spinach, lettuce, and mustard had significantly increased, while the length of the leaves for root beet has shown changes only in terms of the length of the leaves. Spinach, responde the most increasing leaf number from 07 to 45 without and with biochar respectively .Further evidence of the positive effects of biochar as a soil enhancer came from increases in soil pH, conductivity, and specific surface area following biochar addition. This research demonstrates how waste-to-best management may enhance soil quality, increase the production of vegetables grown nearby, and guarantee dried vegetable supply throughout the winter. The results show that using apricot shell biochar reduce adverse environmental impacts and improve yields from agriculture even in harsh conditions.